Patterns for America : Modernism and the Concept of Culture. - Hegeman, Susan (Princeton : Princeton University Press, 2001)
In recent decades, historians and social theorists have given much thought to the concept of "culture," its origins in Western thought, and its usefulness for social analysis. In this book, Susan Hegeman focuses on the term's history in the United States in the first half of the twentieth century. She shows how, during this period, the term "culture" changed from being a technical term associated primarily with anthropology into a term of popular usage. She shows the connections between this movement of "culture" into the mainstream and the emergence of a distinctive "American culture," with i.
Book Cover; Title; Copyright; Contents.
Print version record.
JSTOR
Keywords: American literature -- 20th century -- History and criticism; Modernism (Literature) -- United States; Literature and anthropology -- United States -- History -- 20th century; National characteristics, American, in literature; Modernism (Aesthetics) -- United States; Arts, Modern -- 20th century; Arts, American; United States -- Civilization -- 20th century; Arts, Modern; Littérature américaine -- 20e siècle -- Histoire et critique; Modernisme (Littérature) -- États-Unis.; Littérature et anthropologie -- États-Unis -- Histoire -- 20e siècle.; Modernisme (Esthétique) -- États-Unis.; Arts -- 20e siècle.; Arts américains.; États-Unis -- Civilisation -- 20e siècle.; LITERARY CRITICISM -- American -- General; American literature; Arts, American; Arts, Modern; Civilization; Literature and anthropology; Modernism (Aesthetics); Modernism (Literature); National characteristics, American, in literature; United States; 1900-1999; Criticism, interpretation, etc; History